Growth Performance and Haematology of the Laboratory Rat, Rattus norvegicus fed on Protein Supplements and Heavy Metal - Omotoso, O.T.; Sanya, B.T. (Biological Sciences - PJSIR, 2007)
Labora to ry rat Ra /lu s norvegicus, fed on pou l try growers ma sh pl u s addi ti on a l protei n su pp l em e n t and some h eavy m eta l s, w as stud i ed for t h e growth and t h e h aem ato l ogi cal parnmete r . A l l the d i et ary supp l em ent s resu l ted i n an i n c rea ·e i n the growt h of t h e r ats. Th e ra t s, fed on growers m ash an d praw n m ea l sh owed t h e be st growth w i t h i n 7 week s. E ffects of diets were si gn i fi can t l y, correl ated at 0.0 I l eve l. Wei ght l os was record ed i n case or a l l h eavy m eta l -l aced d i ets, h owever, ca l c i L1m sul ph ate-l a ced diets r esult ed i n a n i n crease i n growth . M t: r cu rous ch l orid e was t.h e m ost tox i c s l t w h i ch re ·u l ted i n t h e greatest w e i ght l oss. J l aemato l ogi ·a l an a l ys i s of rat s revea l ed t h at RBCs we 1·c h i gher i n the case o r h eavy m eta l -l aced d i ets th n h ea v y meta l -free d i et . Gt:n era l l y, RB cou n t w ere h i gh e r i n femal es t h u n i n m a l es w i t h i n a group. F i 'h meal a n d prnwn m ea l feed i ng r esu l ted i n h i gh er WB counts.